Marital status, partner acknowledgment of paternity, and neighborhood influences on smoking during first pregnancy: findings across race/ethnicity in linked administrative and census data - Houston-Ludlam, Alexandra N. (Drug Alcohol Depend, 2020)
BACKGROUND: Improving prediction of cigarette smoking during pregnancy (SDP), including differences by race/ethnicity and geography, is necessary for interventions to achieve greater and more equitable SDP reductions. METHODS: Using individual-level data on singleton first births, 2010–2017 (N = 182,894), in a US state with high SDP rates, we predicted SDP risk as a function of reproductive partner relationship (marital status, paternity acknowledgement), maternal and residential census tract sociodemographics, and census tract five-year SDP rate. RESULTS: SDP prevalence was 12.7% (white non-Hispanics, WNH), 6.8% (Black/African Americans, AA), 19.5% (Native American, NA), 4.7% (Hispanic, H), and 2.8% (Asian, AS). In WNH and AA, with similar trends in other groups, after adjustment for non-linear effects of maternal age and education and for census tract risk-factors, there was a consistent risk-ordering of SDP rates by reproductive partner relationship: married/with paternity acknowledged < unmarried/acknowledged < unmarried/unacknowledged < married/unacknowledged. Associations with census tract SDP rate, adjusted for maternal and census tract sociodemographics, were stronger for AA and H (OR 2.65–2.67) than for NA (OR = 1.91), WNH (OR = 1.75), or AS (NS). AA SDP was increased in tracts having a higher proportion of WNH residents and was reduced in comparison with WNH at every combination of age, education and partner relationship. CONCLUSIONS: Inattention to differences by race/ethnicity may obscure SDP risk factors. Despite marked race/ethnic differences in unmarried-partner cohabitation rates, failure to acknowledge paternity emerged as an important and consistent risk-predictor. Census-tract five-year SDP rates have heterogeneous origins, but the association of AA SDP risk with increased racial heterogeneity suggests an important influence of neighbor risk behaviors.